2014
DOI: 10.1016/j.cellsig.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin expression and cell survival regulation in colorectal cancer

Abstract: Colorectal cancer (CRC) is the second largest cause of cancer deaths in the United States. A key barrier that prevents better outcomes for this type of cancer as well as other solid tumors is the lack of effective therapies against the metastatic disease. Thus there is an urgent need to fill this gap in cancer therapy. We utilized a 2D-DIGE proteomics approach to identify and characterize proteins that are differentially regulated between primary colon tumor and liver metastatic deposits of the IGF1R-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 69 publications
(129 reference statements)
1
40
0
Order By: Relevance
“…Ezrin has been implicated in the regulation of many essential cellular functions including cell adhesion, motility, regulation of ion channels, maintenance and determination of cell shape, morphogenesis, cell proliferation, and apoptosis (2). A growing body of evidence suggests that high ezrin expression correlates with metastatic behavior and poor clinical outcome in a variety of tumors including melanoma, colorectal cancer, endometrioid carcinoma, astrocytic tumors, soft tissue sarcomas, and adenocarcinomas of lung and breast (3)(4)(5)(6)(7)(8)(9)(10)(11). Ezrin has also been directly implicated in tumor progression and metastatic process in pediatric solid tumors of mesenchymal origin including osteosarcoma and rhabdomyosarcoma (12)(13)(14).…”
mentioning
confidence: 99%
“…Ezrin has been implicated in the regulation of many essential cellular functions including cell adhesion, motility, regulation of ion channels, maintenance and determination of cell shape, morphogenesis, cell proliferation, and apoptosis (2). A growing body of evidence suggests that high ezrin expression correlates with metastatic behavior and poor clinical outcome in a variety of tumors including melanoma, colorectal cancer, endometrioid carcinoma, astrocytic tumors, soft tissue sarcomas, and adenocarcinomas of lung and breast (3)(4)(5)(6)(7)(8)(9)(10)(11). Ezrin has also been directly implicated in tumor progression and metastatic process in pediatric solid tumors of mesenchymal origin including osteosarcoma and rhabdomyosarcoma (12)(13)(14).…”
mentioning
confidence: 99%
“…In addition, ezrin plays a key role in cell survival of colon cancer cells and regulates expression of Inhibitor of Apoptosis Proteins (IAP), XIAP and survivin, which have been shown to be involved in cell survival and metastasis (5,22). We have previously shown that IGF1R signaling regulates ezrin phosphorylation at T567 (5). Other studies have shown that ezrin is a downstream effector of the PI3K/AKT pathway (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that transient knockdown of ezrin using siRNA leads to downregulation of XIAP and survivin expression (5). To understand the underlying molecular mechanism, stable knockdown (KD) of ezrin expression was performed using GIFZ lentiviral shRNA#1 and #3 in GEO and FET colon cancer cells.…”
Section: Knockdown Of Ezrin Expression Activates Pka and Induces Apopmentioning
confidence: 99%
See 2 more Smart Citations